Clinical results of single and multiple bioresorbable drug-eluting scaffolds for treatment of de-novo coronary artery disease. Issue 7 (November 2016) - Markovic, Sinisa; Dragomir, Sergiu; Walcher, Daniel; Bernhardt, Peter; Imhof, Armin; Rottbauer, Wolfgang; Wöhrle, Jochen
Abstract : Objectives: Data on multiple bioresorbable vascular scaffolds (BVS) for the treatment of coronary lesions are limited. We compared clinical results after implantation of single or multiple BVS for the treatment of de-novo coronary artery disease. Methods: We enrolled 236 patients with 311 lesions treated with Absorb BVS. Quantitative coronary angiography before and after scaffold implantation was performed. All lesions were predilated. Absorb was implanted with slow inflation and 81% were postdilated with a high-pressure balloon. Patients received dual antiplatelet therapy for 6 months for stable angina pectoris and for 12 months for acute coronary syndrome. Patients were clinically followed for 12 months. Acute gain was 1.39±0.47 mm. Multiple scaffolds per lesion were implanted in 23.8% ( N =74/311 lesions). The mean scaffold length was 21 mm for single and 48 mm (range 28–112 mm) for multiple BVS. Periprocedural myocardial infarction (13.5 vs. 4.6%, P <0.013) and target lesion revascularization (6.8 vs. 0.8%; P =0.003) were significantly higher in the multiple-scaffold group compared with the single-scaffold group. There was no definite scaffold thrombosis. (http://www.clinicaltrials.gov, NCT02162056). Conclusion: Target lesion revascularization within 12 months and periprocedural myocardial infarction were higher for lesions treated with multiple scaffolds compared with lesions treated with single BVS.